Coupling of Enhancer and Insulator Properties Identified in Two Retrotransposons Modulates Their Mutagenic Impact on Nearby Genes - Conte, Caroline (American Society for Microbiology, 2002)
We recently reported a novel transposition system in which two retroelements from Drosophila melanogaster, ZAM and Idefix, are highly mobilized and preferentially insert within intergenic regions. Among the loci where new copies are detected, a hot spot for their insertion was identified at the white locus, where up to three elements occurred within a 3-kb fragment upstream of the transcriptional start site of white. We have used these insertions as molecular entry points to throw light on the mutagenic effect exerted by multiple insertions of retrotransposons within intergenic regions of a genome. Analysis of the molecular mechanisms by which ZAM and Idefix elements interfere with the regulation of the white gene has shown that ZAM bears cis-acting regulatory sequences able to enhance transcription of the white gene in the eyes of the flies. This activation may be counteracted by Idefix, which acts as an insulator able to isolate the white gene from the upstream ZAM enhancer. In addition to revealing a novel insulator sequence with its own specific features, our data clearly illustrate how retroelements can act as epigenetic factors able to interfere with the transcriptional regulation of their host.